2008
DOI: 10.4278/ajhp.07060352
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Salt Consumption to Guide Behavior Change in Applied Settings: A Critical Review

Abstract: Further research is needed to improve the specificity of measures of behaviors that are indicative of salt consumption and to produce tools that clinicians and patients may use for more accurate, and possibly real-time, salt consumption measurement. The increasing burden of cardiovascular disease in the aging U.S. population demands better methods to assess and subsequently control salt consumption in applied settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…6 In addition to this one-item measure, we included 4 items to assess consumption of salty products in the past week and used these to construct a saltconsumption index (cf. Parkington & Roussos, 2008). Using this index in the analyses yielded similar results and identical conclusions.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…6 In addition to this one-item measure, we included 4 items to assess consumption of salty products in the past week and used these to construct a saltconsumption index (cf. Parkington & Roussos, 2008). Using this index in the analyses yielded similar results and identical conclusions.…”
Section: Discussionsupporting
confidence: 59%
“…Still, further research is needed to increase validity and reliability of current saltconsumption measurements (cf. Parkington & Roussos, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This method is however also not 100% bias-proof. Additionally, self-reported salt consumption has been used in previous research and has been found to yield reliable results (Parkington & Roussos, 2008;Salonen et al, 1983). For our purposes self reports probably sufficed.…”
Section: Self-report Measuresmentioning
confidence: 93%